2021
DOI: 10.3389/fonc.2021.657595
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Immune Infiltration of Chromobox Family Genes in Sarcoma

Abstract: BackgroundChromobox family genes (CBXs) are known to play roles in numerous modifications of the chromatin in order to inhibit the transcription of target genes. CBXs have been shown to be expressed at high levels in many types of cancer and can also serve as a target gene for therapeutic purposes. However, little is known about the expression and prognostic value of CBXs in human sarcomas.MethodsThe transcription level of CBXs was analyzed using the Oncomine dataset, and the differential expression of CBXs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The CBXs family were reported to participate in the tumor progression and the several immune cells infiltration in various cancer types, thus affecting patient prognosis and therapy (Chen et al, 2019;Zhou et al, 2021). In this study, we applied TIMER2.0 to explore the correlation between the individual CBXs family members and the immune infiltration of ovarian cancer.…”
Section: Immune Infiltration Levels Of the Cbxs Family In Ovarian Cancer Patientsmentioning
confidence: 99%
“…The CBXs family were reported to participate in the tumor progression and the several immune cells infiltration in various cancer types, thus affecting patient prognosis and therapy (Chen et al, 2019;Zhou et al, 2021). In this study, we applied TIMER2.0 to explore the correlation between the individual CBXs family members and the immune infiltration of ovarian cancer.…”
Section: Immune Infiltration Levels Of the Cbxs Family In Ovarian Cancer Patientsmentioning
confidence: 99%
“…Emerging evidence supported that immune cell levels were correlated with tumorigenesis and progression in multiple tumor types [7,22]. In this analysis, through the TIMER2.0, we investigated the correlations between different CBX members and immune cell infiltration levels in GBM.…”
Section: Immune Cell Infiltration Of Cbxs In Patients With Gbmmentioning
confidence: 99%
“…Thus, the identification of novel biomarkers for enhancing prognosis and individualized treatment effectively is of great significance. So far, eight CBX family members (CBX1-8) have been found in mammalian cells [6,7]. They are all participated in cell cycle regulation transcriptional repression, heterochromatin, and apoptosis [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells in TME may play tumor-promoting and suppressive roles, thereby influencing the clinical outcome ( Yang et al, 2019 ). The CBX family members have been reported to contribute to the infiltration of immune cells in various cancers ( Li Q et al, 2020 ; Zhou et al, 2021 ). In our study, we showed that the CBX family members’ expression could be significantly related to the infiltration of immune cells in ESCA, indicating that CBXs might also affect the immune status.…”
Section: Discussionmentioning
confidence: 99%